Determinants of Financial Well-Being: A Systematic Review of SEM Evidence - Sarlawa, Rita; Ali, Muhammad (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study aims to conduct a comprehensive systematic literature review of research on financial well-being using structural equation modeling from 2020 to 2025. Based on more than 80 empirical studies, the review establishes a unified framework that links financial literacy, psychosocial traits, behavior, digital inclusion, and resilience. This method review follows PRISMA guidance and applies SEM-specific criteria. The findings indicate that financial well-being is primarily influenced by behavioral mediation pathways, where literacy and skills enhance budgeting, saving, and debt management. Psychosocial factors, such as self-efficacy, locus of control, and hope, serve as mediators that strengthen these behavioral pathways. Additionally, digital financial literacy expands access and encourages informed financial decisions. Despite progress, differences persist across demographics and regions, influenced by factors such as gender, age, religiosity, and socio-economic status. Methodological differences between CB-SEM and PLS-SEM result in discrepancies in effect sizes, underscoring the importance of transparency and robustness. Policy efforts, such as counseling, safety nets, and debt relief, improve financial well-being. The review advocates for future research using panel structural equation modeling, experimental designs, and cross-country tests to strengthen causal claims and applicability. This synthesis provides a framework that supports the integration of theory and evidence-based policies to enhance financial resilience and inclusion.